A conjugated polymer based on alkylthio-substituted benzo[1, 2-c:4, 5-c']dithiophene-4, 8-dione acceptor for polymer solar cells. (June 2019) - Ma, Junshu; Feng, Guitao; Liu, Feng; Yang, Fan; Guo, Yiting; Wu, Yonggang; Li, Weiwei
Abstract: In this work, the 2, 5-di(alkyl)thiophene unit was replaced with a 2, 5-di(alkylthio)thiophene moiety on benzo [1, 2- c :4, 5- c ']dithiophene-4, 8-dione (BDD) unit. The di(alkylthio) substituted BDD was used to obtain a novel copolymer PSBDB-T via Stille polymerization. PSBDB-T shows good solubility and excellent thermal stability. The opto-electronic properties of PSBDB-T were investigated. PSBDB-T has a broad absorption range from 300 nm to 700 nm and deep highest occupied molecular orbital (HOMO) level due to the alkylthio units, which can improve the open-circuit voltage. A solar cell based on PSBDB-T as donor and a near infrared absorbing non-fullerene acceptor achieves a power conversion efficiency (PCE) of 5.0%, which is lower than its analogous polymer PBDB-T with a PCE of 8.8%. The studies of organic field-effect transistors and space charge limited current (SCLC) measurement indicate that PSBDB-T shows a significantly low hole mobility, which is responsible for the low photocurrent and fill factor in solar cells. Graphical abstract: Image 1 Highlights: A di(alkylthio) substituted benzo [1, 2- c :4, 5- c ']dithiophene-4, 8-dione was developed for a wide band gap conjugated polymer PSPBDB-T. Surprisingly, PSBDB-T performed relatively a low PCE of 5.0% compared to the dialkyl substituted with a PCE of 8.0%. The low efficiency was due to the low crystallinity, poor charge transport and severe charge recombination in solar cells.